أسلوب معاملة البنات (الإحسان – الجحود) للوالدین وعلاقتھ باستقرارھن النفسي (Journal of the College of Education for Women, 2019)
Target current research to identify the style (charity - ingratitude) in thetreatment of parents and to identify the psychological stability as well as to identifythe correlation between two variables, And identifies current research by studentsfourth grade - and the first phase of study of students in the College of Educationfor Girls in the morning preliminary study for the academic year (2009-2010) mTotal numbers (400) students. After the application of research tools and dataprocessing means of appropriate statistical research concluded that the handling ofstudents with parents, a charity And treatment of students to mothers were treatedto the best of fathers as well as the enjoyment of a high level of psychologicalstability and the existence of correlation between the style of (charity) in thetreatment of parents and psychological stability. In the light of the results of theresearch, the researcher puts many suggestions and recommendations.